A high-efficiency utilization of coke-oven plant coke ash for the preparation of coke ash emulsion slurry. (1st June 2019) - Fan, Yaoyao; Wang, Ruiqi; Li, Xiaolin; Xiang, Jin; Shao, Qi; Meng, Shuang; Chen, Chuang; Yang, Qi; Liang, Peng; Sun, Huanwu
Graphical abstract: Highlight: A high-efficiency utilization of coke-oven plant coke ash was proposed. Effect of particle size and temperature on the slurryability of slurry was studied. Slurry storage and delivery features as rheological and thixotropic were studied. Coke emulsion slurry has better storage stability than coke water slurry. Abstract: Coke ash (CA) from the dust collection station of coking plants has a high carbon content and can be used as a fuel feedstock for secondary uses, avoiding environmental pollution. In this study, CA was blended with diesel oil and water to prepare a coke emulsion slurry (CES) synfuel in the presence of primary alcohol ethoxylate (AE) and polycarboxylate dispersant (PC) for gasification or combustion, as an efficient method for the utilization of CA. The effects of the particle size distribution of CA, oil to water ratio (O:W) and temperature on the slurryability of CES were investigated, and properties, such as rheology, thixotropy and stability, of CES were examined. The results showed that with a decrease of CA particle size, its slurryability is greatly improved. The apparent viscosity of CES increased when the oil content and the CA content (ω) increased. The maximum value of ω in the CES declined incrementally in oil proportion, ranging from ω = 74 wt% for the coke-water-slurry (CWS) to ω = 62 wt% at CES with O:W = 1:3. Furthermore, the higher the temperature was, the lower the apparent viscosity of the slurry. CES and CWS both exhibited non-Newtonian pseudoplastic fluid behaviour. Its pseudoplasticity and thixotropy also increased as the ω of CES rose. The oil content and ω had a great influence on the stability of CES. The dispersion behaviour and stabilization mechanism were revealed by the contact angle, zeta potential measurements and optical microscope image. Overall, this study provided a direct and efficient utilization method for CA.